A Unique Case of Optic Disc Pit in One Eye with CSC in Other Eye - Akhwand Abdul Majeed Jawad, Haroon Tayyab (Pakistan Journal of Ophthalmology, 2015)
A 41 year old male patient presented in eye OPD of Sharif Medical City Hospital in January 2015 with complaints of recent onset subacute painless decrease in vision along with metamorphopsia in his right eye. On detailed ophthalmic examination, he was found to have Central Serous Chorioretinopathy (CSC) in his right eye and optic disc pit in the left eye. He was investigated with FFA and OCT and treated with focal argon laser in his right eye and systemic rifampicin 300mg for 3 months. His symptoms recovered after one month of laser and systemic therapy. We report this unique case of CSC in one eye and optic disc pit without maculopathy in other eye. Despite successful treatment of CSC, this patient stands at risk of developing more severe maculopathy in the left eye which may warrant surgical treatment in future. Keywords: Central serous chorioretinopathy, Optic disc pit, Optical coherence tomography.